1985
DOI: 10.1111/j.1469-7610.1985.tb01943.x
|View full text |Cite
|
Sign up to set email alerts
|

Inspection Time and Intelligence in Dyslexic Children

Abstract: Dyslexics and normal readers aged 9-11 were compared on an inspection time task. Results indicated that dyslexics required significantly longer inspection times. The findings suggested, however, that there was greater individual variation among dyslexics than among normal readers and that the dyslexics benefited from practice to a considerable extent. Inspection times were not significantly related to IQ as measured by a non-verbal test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
2
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
3
2
1
Order By: Relevance
“…The Dyslexia group had slightly slower inspection times than the Control group, but this difference failed to reach significance, t (80) ϭ 1.493, p Ͼ .05, d ϭ .327. However, similar to previous findings exploring inspection time in dyslexia (Kranzler, 1994;Whyte et al, 1985), the inspection time thresholds were found to be positively skewed (Kolmogorov-Smirnov Z ϭ 1.81, p Ͻ .05), and five participants recorded extremely slow inspection times (more than 120 ms). Consequently, participants whose inspection time thresholds exceeded 120 ms were all given an equal value of 120 ms; however, group comparisons of the new inspection time thresholds again did not reveal any significant differences between Dyslexia and Control groups, t ( 80 Attentional blink differences between the groups were explored by examining mean second target accuracy at each of the lags (200 ms, 400 ms, 600 ms, and 800 ms) 7 when the first target had been correctly identified (T2͉T1).…”
Section: Inspection Timesupporting
confidence: 86%
See 1 more Smart Citation
“…The Dyslexia group had slightly slower inspection times than the Control group, but this difference failed to reach significance, t (80) ϭ 1.493, p Ͼ .05, d ϭ .327. However, similar to previous findings exploring inspection time in dyslexia (Kranzler, 1994;Whyte et al, 1985), the inspection time thresholds were found to be positively skewed (Kolmogorov-Smirnov Z ϭ 1.81, p Ͻ .05), and five participants recorded extremely slow inspection times (more than 120 ms). Consequently, participants whose inspection time thresholds exceeded 120 ms were all given an equal value of 120 ms; however, group comparisons of the new inspection time thresholds again did not reveal any significant differences between Dyslexia and Control groups, t ( 80 Attentional blink differences between the groups were explored by examining mean second target accuracy at each of the lags (200 ms, 400 ms, 600 ms, and 800 ms) 7 when the first target had been correctly identified (T2͉T1).…”
Section: Inspection Timesupporting
confidence: 86%
“…Inspection time has not been extensively studied in dyslexia, with investigations typically focusing on more general associations with intelligence (see Grudnik & Kranzler, 2001 for a meta-analysis). One study has reported significantly longer inspection times in children with dyslexia, but the authors were cautious in their conclusions, suggesting that inconsistent performance in the dyslexia group may have been attributable to more general task demands or concentration difficulties (Whyte, Curry, & Hale, 1985). The influence of concentration deficits and task difficulty was also noted in a later study by Kranzler (1994), who reported no significant differences in inspection time between children with dyslexia and controls.…”
Section: The Magnocellular Deficit Theory Of Dyslexiamentioning
confidence: 99%
“…Second, significant visual differences may be less evident in highly skilled adult readers than in children. Third, the relationship between intelligence, particularly performance IQ, and visual temporal processing has been documented in some visual inspection time studies (Bowling & Mackenzie, 1996;Deary, 1993;Stough et al, 1996; but see also Mackenzie et al, 1989;Whyte, Curry, & Hale, 1985). Accordingly, visual temporal processing and intelligence may undermine each other and thus the statistical control of IQ might have masked the visual differences in the present study.…”
Section: Discussioncontrasting
confidence: 41%
“…(ill) The finding that dyslexics had a slower reaction time; a similar finding was reported by Whyte, Curry and Hale (1985), though it was clear from the latter study that there was greater individual variation among the dyslexics than among nonnal readers and that dyslexics bene fitted from practice and might well eventually have equalled the nonnal readers Wright et al's study also contributes to our knowledge of the perfonnance of dyslexics on tasks requiring phonological ability. Their finding that phonological access is more difficult for dyslexics is not unexpected, but the finding that the dyslexics did not appear to show greater inclination to use other strategies than their controls challenges the assumption that poor phonological development is balanced by superior development in other areas of functioning.…”
supporting
confidence: 63%